Comparison of two different sampling methods for subgingival plaque: subgingival paper points or mouthrinse sample? - Nickles, Katrin; Dannewitz, Bettina (Journal of periodontology, 2017)
The collection of subgingival plaque samples with paper points is time-consuming and accident-sensitive. However, the collection of saliva is simple and contains pathogens of all intraoral surfaces. The aim of this study is to investigate whether a sampling strategy with mouthrinse (mouthrinse sample [MSP]; test) leads to results comparable with standard sampling method (multiple site test from the deepest pocket of each quadrant [MT4]; control).